2011
DOI: 10.1021/nl201383u
|View full text |Cite
|
Sign up to set email alerts
|

Are Nanoporous Materials Radiation Resistant?

Abstract: The key to perfect radiation endurance is perfect recovery. Since surfaces are perfect sinks for defects, a porous material with a high surface to volume ratio has the potential to be extremely radiation tolerant, provided it is morphologically stable in a radiation environment. Experiments and computer simulations on nanoscale gold foams reported here show the existence of a window in the parameter space where foams are radiation tolerant. We analyze these results in terms of a model for the irradiation respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
135
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(141 citation statements)
references
References 20 publications
(28 reference statements)
3
135
0
3
Order By: Relevance
“…This has motivated an intense ongoing search for new classes of materials with improved radiation hardness. New materials, shown to have high radiation tolerance include nanocrystalline materials [14][15][16], multilayered nanomaterials [17], and nanofoams [18,19]. Although all of these are promising for some applications, the high fraction of surface or interface, which are thermodynamically unstable, makes nanostructures in general unreliable for long operational times at elevated temperatures.…”
mentioning
confidence: 99%
“…This has motivated an intense ongoing search for new classes of materials with improved radiation hardness. New materials, shown to have high radiation tolerance include nanocrystalline materials [14][15][16], multilayered nanomaterials [17], and nanofoams [18,19]. Although all of these are promising for some applications, the high fraction of surface or interface, which are thermodynamically unstable, makes nanostructures in general unreliable for long operational times at elevated temperatures.…”
mentioning
confidence: 99%
“…Recently, with the growing use of nanostructured systems in various types of technological devices, the understanding of specificities in energy deposition and damage production by radiation in matter at the nanoscale has become a critical issue. Unique effects of energetic ions on nanoscale systems have already been reported and successfully applied to engineering of materials [10][11][12][13]. Nevertheless, very little has been reported so far on a direct comparison of radiation effects of heavy ions in a material at bulk and spatially confined conditions.…”
mentioning
confidence: 99%
“…In these materials, nanoprecipitate-matrix interfaces provide effective sinks for transmutation products and irradiation-induced defects. [5] A recent study [6] has shown that enhanced radiation resistance can also be exhibited by nanoporous materials, since free surfaces can act as unsaturable defect sinks. In addition, a number of experimental [7,8] and simulation [9][10][11][12] studies have shown that bulk nanocrystalline (nc) materials * Corresponding authors.…”
mentioning
confidence: 99%